Answer:
Step-by-step explanation:
follow the Pemdas order of operations
add and subtract (left to right)
apply the rule +(-a)=-a
+(-78)=-78
=54-78-(-39)
54-78=-24
=-24-(-39)
apply the rule -(-a)=+a
-(-39) =+39
=-24 +39
-24+39=15
=15
Answer:
y=2x/3 + 2
Step-by-step explanation:
3y= 2x +6
y=2x/3 + 2
So step one is to distribute the 4x through and the -5 through. After distributing you get 8x^{2}+28x-15x+10. Combine the like terms, 28x and -15x, to get 13x. Your answer is 8x^{2}+13x+10
Step-by-step explanation:
Hey ..but there is nothing from which question can be equated ..
like if they are equal to zero..
or
(4x+45)=(5x-18)
i am giving answer for both scenarios
(4x+45)=0
4x=-45
x=-45/4
x=(-11.25)
(5x-18)=0
5x=18
x=18/5
x=3.6
Incase if they both are equal to each other...
(4x+45)=(5x-18)
(45+18)=(5x-4x)
63=x
x=63
Hope it helps you
Have a nice day
Sure, there's such a thing as an isosceles right triangle. It's what you get when you draw the diagonal of a square. It has one right angle (of course) and two 45 degree angles. It's the shape that vexed the Pythagoreans.